WHEN IS AN ABELIAN WEAKLY CLEAN RING CLEAN? - Danchev, Peter (Journal of the Indonesian Mathematical Society, 2015)
We answer the title question in the armative by showing that anyabelian weakly clean ring for which 2 belongs to its Jacobson radical (in particular, if 2 is nilpotent) has to be clean. Some constructive examples, one of which illustrates that this is no longer true removing the condition on the 2, are given as well.DOI : http://dx.doi.org/10.22342/jims.21.2.229.83-91